Perceptual learning and generalization resulting from training on an auditory amplitude-modulation detection task - Fitzgerald, Matthew B. (Acoustical Society of America, 2011)
Fluctuations in sound amplitude provide important cues to the identity of many sounds including speech. Of interest here was whether the ability to detect these fluctuations can be improved with practice, and if so whether this learning generalizes to untrained cases. To address these issues, normal-hearing adults (n = 9) were trained to detect sinusoidal amplitude modulation (SAM; 80-Hz rate, 3–4 kHz bandpass carrier) 720 trials∕day for 6–7 days and were tested before and after training on related SAM-detection and SAM-rate-discrimination conditions. Controls (n = 9) only participated in the pre- and post-tests. The trained listeners improved more than the controls on the trained condition between the pre- and post-tests, but different subgroups of trained listeners required different amounts of practice to reach asymptotic performance, ranging from 1 (n = 6) to 4–6 (n = 3) sessions. This training-induced learning did not generalize to detection with two untrained carrier spectra (5 kHz low-pass and 0.5–1.5 kHz bandpass) or to rate discrimination with the trained rate and carrier spectrum, but there was some indication that it generalized to detection with two untrained rates (30 and 150 Hz). Thus, practice improved the ability to detect amplitude modulation, but the generalization of this learning to untrained cases was somewhat limited.